Nanoparticles Navigating the Intranasal Route: Innovative Approaches in Neurodegenerative Diseases - Fabiola V. Borbolla-Jiménez; Stephany Celeste Gutiérrez-Ruiz; Hector Hernández-Parra; Sheila I. Peña-Corona; Aura A. Tamez; Ricardo D. Rivas-Amores; Jonathan J. Magaña; Gerardo Leyva-Gomez (Journal of Nanotechnology)
Intranasal drug delivery is emerging as a transformative strategy for treating neurodegenerative diseases, offering a noninvasive route that bypasses the limitations of the blood–brain barrier. This review provides a comprehensive analysis of the current landscape and challenges of intranasal drug delivery for neurodegenerative conditions with an emphasis on nanoparticle (NP)-based formulations. Unlike traditional systemic methods, intranasal delivery uses the nasal cavity’s anatomy to achieve rapid and direct central nervous system transport via the olfactory and trigeminal pathways. This review evaluates NP strategies designed to overcome physiological barriers such as mucociliary clearance, enzymatic degradation, and limited nasal volume capacity. Innovations in mucoadhesive coatings, surface modifications, and stimuli-responsive NP that optimize drug release and retention time within the nasal cavity are highlighted. In addition,​ cutting-edge NP systems under clinical investigation and their translational potential are explored, addressing challenges like reproducibility, safety, and patient adherence. New research directions for optimizing NP formulations to improve outcomes in diseases like Alzheimer’s, Parkinson’s, and hereditary ataxias are proposed. Lastly, broader implications of these technologies for conditions such as psychiatric disorders and brain injuries are discussed. By integrating nanotechnology and intranasal administration, this review aims to inspire future research to bridge the gap between preclinical promise and clinical success, advocating for continued innovation to unlock the full therapeutic potential of this promising approach for treating neurological disorders.